EFL Pre-Service Teacher Anxiety During Kampus Mengajar Program at Junior High School - Elanda Yopita; Andi Rachmawati Syarif; Rahmat Nasrullah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aimed to identify the causes of pre-service teacher anxiety during the Kampus Mengajar Program at SMPN 22 Kendari. Employing a qualitative case study approach, this research involved six female pre-service teachers from Haluoleo University and Muhammadiyah University of Kendari who participated in the fourth batch of the Kampus Mengajar Program from August to December 2022. Data were collected through semi-structured interviews conducted in Indonesian and analyzed using Miles et al. data analysis technique consisting of data condensation, data display, and conclusion drawing. The findings revealed two major categories of anxiety: external factors including heavy teaching load and worry about teaching effectiveness, and internal factors comprising low self-confidence and low confidence in English competence. These anxiety factors significantly impacted pre-service teachers’ classroom performance and emotional well-being throughout the five-month teaching placement. The study provides important implications for teacher education programs to develop comprehensive support systems addressing both environmental pressures and psychological vulnerabilities of pre-service teachers during extended teaching placements.